Celiac Disease Methods and Protocols - Marsh, Michael N. (Methods in Molecular Medicine, 2000)
With the recent development of powerful bioanalytical techniques, research on gluten sensitivity has entered an exciting new phase. In Celiac Disease: Methods and Protocols, Professor Michael N. Marsh, a recognized world authority on this condition, together with a team of other expert laboratory/clinical investigators from around the world present a collection of these state-of-the-art techniques for studying the biology and immunopathology of celiac disease. Both novice and experienced researcher will find in this collection detailed step-by-step methods for cloning lymphocytes, creating gene/peptide libraries, and performing genotyping, linkage, and positional cloning. Also included are techniques for determining the peptide structure of HLA-bound material (tandem mass spectroscopy), computerized morphometry, in situ hybridization, organ culture, and monoclonal AB assays. Comprehensive and cutting-edge, Celiac Disease: Methods and Protocols provides all experimental and clinical investigators with the essential core of readily reproducible methods necessary for successful work on celiac disease today